Global burden of five major types of gastrointestinal cancer - Arjun Singh (Gastroenterology Review)
Gastrointestinal (GI) cancers cause major global morbidity and mortality, with over 5 million new cases and 3.5 million deaths in 2020. The most prevalent GI malignancies are colorectal, gastric, liver, oesophageal, and pancreatic cancers. Marked geographic variations exist, with high incidence in developed regions contrasting with high mortality in developing areas. These patterns reflect disparities in risk factors and cancer control capacities. However, GI cancer incidence is rising with economic growth and lifestyle changes. Poor prognosis and increasing burden underscore the critical need for expanded prevention and research. This review examines global epidemiology, risks, prevention, detection, treatment, and priorities for common GI cancers. Controlling the toll of GI malignancies requires coordinated global actions across prevention, screening, treatment access, and research. Key priorities include vaccination, reducing modifiable risks, improving screening, expanding care access, and advancing prevention/therapy research. Global commitments to evidence-based interventions and knowledge sharing are vital to curb the GI cancer epidemic.